Nanoconfinement-enhanced peroxymonosulfate activation by Co single atoms in hollow mesoporous carbon: Roles of active-site chemistry and mesoscale confinement - Hao Luo; Junli Zheng; Jiaxin Liu; Junjun Ma; Rui He; Chuqi Huang; Rong Xie; Qintie Lin (Water Research, 2026)

Delayed and asymmetric groundwater responses to meteorological forcing across Germany revealed by lagged mutual information - Fangfei Cai; Funing Ma; Zhenxue Dai; Junjun Chen (Journal of Hydrology, 2026)

Feasibility evaluation for cockroach from Periplaneta americana as a new protein feed ingredient in pigs - Zilin Li; Yu Cao; Meng Liu; Jingru Yuan; Jia Li; Wentao Huo; Mingyi Huang; Shuaishuai Kang; Shiyan Sui; Xiaokang Ma; Yujun Wu; Dandan Han; et al. (Animal Feed Science and Technology, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Astrocytic Prostaglandin Transporter SLCO2A1–Ca2+ Maintains Blood–Brain Barrier Integrity Against Ischemia - Taozhi Wang; Manping Yang; Haiyun Guo; Hongyu Ma; Zhenzhen Li; Junjun Kang; Yaomin Guo; Shengxi Wu; Yazhou Wang; Wugang Hou (Neuroscience Bulletin, 2026)

Autonomous inverse modeling of complex groundwater systems via a physics-integrated large language model multi-agent framework - Funing Ma; Junjun Chen; Zhenxue Dai; Fangfei Cai; Yingtao Hu (Water Research, 2026)

Low-frequency vibration-induced crack expansion: Insights from resonance frequency and amplitude effects - Junjun Feng; Ting Zhang; Wangyuan Liu; Xinyu Zhang; Yankun Ma; Xiaofei Liu (Gas Science and Engineering, 2026)

Long-term bioaugmentation of a carrier enhanced duckweed-based wastewater treatment system via the addition of activated sludge and denitrifying phosphate-accumulating bacterium - Yonggui Zhao; Ruidong Ma; Xixi Li; Jinquan Li; Tianning Liang; Wei Li; Junjun Chang; Changqun Duan (Ecological Engineering, 2026)

Multiscale simulation and machine learning sensitivity analysis of pore-structure controls on solute transport in heterogeneous porous media - Sida Jia; Yuyang Huang; Junjun Chen; Zhongjun Ma; Jian Tian; Zhenxue Dai (Journal of Hydrology, 2026)

Boron-doped secondary shell coordination architectures in iron single-atom catalysts boosts peroxymonosulfate activation and high-valent iron-oxo species formation for superior aquatic micropollutant purification - Junli Zheng; Shanhong Lan; Junjie Hu; Junjun Ma; Yajie Wu; Ceng Zeng; Hao Luo; Jinquan Wan; Qintie Lin; Junlong Xie (Journal of Environmental Sciences, 2026)

From single-interface LN2 fracturing to CBM stimulation: Temperature optimization and cracking mechanism - Junjun Feng; Hongqing Qiu; Peng Zhang; Wei Li; Xiaofei Liu; Yankun Ma (Fuel, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Physically crosslinked polyphenol-chitosan edible coating for the application of walnut kernels during roasting - Xinhui Wang; Junjun Zhou; Bing Qi; Zhou Chen; Siting Li; Aijin Ma; Yingmin Jia (Food Chemistry, 2026)

Role of flow electrode chamber channel depth in charge transfer and ion migration in FCDI: Mechanistic insights and energy efficiency evaluation - Cheng Wang; Jianrui Niu; Situ Mu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Exploring diverse physical technologies for microbial inactivation and toxin degradation in rice: A comprehensive review - Bengang Wu; Chenyu Song; Yiting Guo; Lei Cong; Junjun Dai; Shenao Nan; Yan Shen; Haile Ma (Food Control, 2026)

Redox electrolyte enhances dual-anode FCDI (DA-FCDI) desalination of brackish and synchronously removal NOM - Kexin Kang; Situ Mu; Jianrui Niu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

On field measurement for absorption properties of biomass burning aerosols in the North China Plain and climate implications - Yang Wang; Yansong Xu; Ruonan Bian; Junjun Deng; Yichen Ma; Song Guo; Jing Wang (Science China Earth Sciences, 2026)

Enhancing drying behavior and textural properties of carrot slices by infrared drying combining contact ultrasound - Bengang Wu; Chenyu Song; Yiting Guo; Kun Gao; Ningning Ouyang; Shenao Nan; Junjun Dai; Yan Shen; Haile Ma (Food and Bioproducts Processing, 2025)

The CD40/CD40L Pathway Regulates the Aggressiveness of Ovarian Cancer Cells via the Activation of Regulatory B Cells - Shanshan Ma; Pengfei Chen; Suyang Guo; Liangliang Wang; Jialin Hu; Junjun Shao (Biochemical Genetics, 2025)

Impact of groundwater extraction intensity on the monitoring design for seawater intrusion in heterogeneous coastal aquifers - Funing Ma; Junjun Chen; Zhenxue Dai; Fangfei Cai; Dayong Wang; Yue Ma (Journal of Hydrology, 2025)

Challenges of high temperature on ultrasonic propagation in coal reservoirs: Insights from moisture desorption and fissure expansion - Junjun Feng; Shigeng Li; Yankun Ma; Yuanfang Qu; Qisong Huang; Houcheng Ding (Gas Science and Engineering, 2025)

Evolutionary repeatability of chromatin accessibility in the hippocampus between echolocating bats and soft-furred tree mice - Luye Shi; Yuanshuo Ma; Qinyang Hua; Junjun Hao; Qin Zhang; Yaxin Ye; Lu Yang; Qi Liu; Peng Chen; Zhen Liu; Peng Shi (Science China Life Sciences, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Hydroxysafflower yellow A alleviates the inflammatory response in astrocytes following cerebral ischemia by inhibiting the LCN2/STAT3 feedback loop - Lijuan Song; Yige Wu; Lijun Yin; Yanzhe Duan; Jianlin Hua; Mengwei Rong; Kexin Liu; Junjun Yin; Dong Ma; Ce Zhang; Baoguo Xiao; Cungen Ma (Metabolic Brain Disease, 2025)

Coupling effect of moisture desorption and matrix contraction on resistivity of water-bearing coal under high geothermal environment - Junjun Feng; Yuanfang Qu; Shigeng Li; Chuanhua Xu; Yankun Ma; Qisong Huang; Long Dang (Journal of Applied Geophysics, 2025)

Astronomically forced dynamics of Late Devonian (Famennian) sea level and biotic recovery in western Junggar, Northwest China - Kunyuan Ma; Linda Hinnov; Zhihong Wang; Kai Wang; Ruiwen Zong; Xinsong Zhang; Junjun Song; Yang Bai; Yiming Gong (Global and Planetary Change, 2025)

Unveiling the role of intrinsic defects in N/S Co-Doped hard carbon for superior sodium-ion batteries - Yunlei Yang; Chang Liu; Junjun Yao; Zhenqi Tang; Ying Sun; Kun Zhang; Hui Li; Tianyi Ma; Jieshan Qiu (Chemical Engineering Journal, 2025)

Structural disorder Triggered by small organic molecules Boosting δ-MnO2 cathode for Ultra‐Stable aqueous zinc ion batteries - Junjun Tang; Shuan Ma; Yu Jiang; Lufeng Yang; Jie Chen; Xuemin Yan; Bohong Chen; Zhenxiong Huang (Chemical Engineering Journal, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Optimizing growth and antioxidant function in heat-stressed broilers with vitamin C and betaine supplementation - Yan Li; Junjun Yuan; Shiang Sun; Feiyang Ma; Yongjie Xiong; Shaojun He (International Journal of Biometeorology, 2024)

Analysis of the critical parameters for tritiated water entrained moist gas emission from nuclear power station - Xi Xu; Kefeng Lv; Yang Li; Xudan Ma; Hualei Jiang; Chunhua Chen; Junjun Zhang (Annals of Nuclear Energy, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Optimization of the intermediate chamber improves desalination performance in flow electrode capacitive deionization (FCDI): A comparative study - Yunke Li; Chenxu Yang; Meng Chen; Yonghuan Bian; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Desalination, 2024)

Temperature sensitivity of aerobic and anaerobic organic carbon mineralization varies with climate and soil depth in riparian zones - Mingzhu Lu; Gang He; Lei Fan; Guihua Liu; Junjun Wu; Wenzhi Liu; Lin Ma (Soil Biology and Biochemistry, 2024)

Recognition and Prediction of Multi-Level Handling Complexity at Automated Terminals Based on ARIMA - Yong Ma; Junjun Li (Journal of Marine Science and Engineering, 2024)
Accurate recognition and prediction of the multi-level handling complexity in automated container terminals (referred to as “automated terminals”) is a prerequisite for improving the effectiveness of scheduling and realizing intelligent operation and maintenance. According to the operating characteristics of the automated terminal equipment, the operating network is constructed of automated terminals that describe the characteristics of operating complexity. We use K-medoids and a light gradient boosting machine (LightGBM) to construct a K-LightGBM model that recognizes multi-level handling complexity. The key lies in the reasonable construction of prediction models. A hyper-heuristic autoregressive integrated moving average (ARIMA) model is proposed to address the problem that the ARIMA is ineffective in predicting nonlinear data. We combine ARIMA and the LightGBM model to establish an ARIMA-LightGBM model to predict multi-level handling and residuals. To improve accuracy, we propose the two residual prediction strategies of direct prediction and limited residual boundary prediction based on the residuals generated by ARIMA. We propose a hyper-heuristic algorithm based on a gradient descent-trust region (GD-TR) to compute the weights of predicted values under the two strategies, which improves the global search capability by GD and TR. The particle swarm optimization algorithm, simulated annealing algorithm, and ant colony optimization algorithm are low-level heuristics. Simulation results show that the proposed model possesses the lowest root mean square error on all characteristics compared to ARIMA, E-ARIMA, and ARIMA-LSTM. Therefore, the proposed model is very effective in improving the accuracy of predicting the multi-level handling complexity at automated terminals.

Differential responses of temperature sensitivity of greenhouse gases emission to seasonal variations in plateau riparian zones - Yongtai Pan; Junjun Wu; Guihua Liu; Wenzhi Liu; Lin Ma (Environmental Pollution, 2024)

Modulation of evapotranspiration and stream runoff by weathered bedrock in arid and semi-arid mountains - Pengfei Lin; Peng Zhao; Jian Ma; Junjun Yang; Xi Zhu; Quanyan Tian; Jun Du; Longfei Chen; Zhibin He (Science of The Total Environment, 2024)

Carbon felt (CF) acted as an “ionic capacitor” to enhance flow electrode capacitive deionization (FCDI) desalination performance - Yunke Li; Junjun Ma; Minghao Yu; Jianrui Niu; Jiarong Gu; Meng Chen; Puming Zhang; Jing Zhang; Chun Liu (Desalination, 2024)

Utilizing machine learning for reactive material selection and width design in permeable reactive barrier (PRB) - Yangmin Ren; Mingcan Cui; Yongyue Zhou; Shiyu Sun; Fengshi Guo; Junjun Ma; Zhengchang Han; Jooyoung Park; Younggyu Son; Jeehyeong Khim (Water Research, 2024)

Nitrogen-rich penicillin residue biochar for activation of peroxymonosulfate for an efficient degradation of tetracycline and its dual-pathway mechanism - Jianrui Niu; Hua Jia; Minghao Yu; Jinyu Zhu; Junjun Ma; Zhuang He; Weizhang Zhong; Yongjiang Hou; Yankai Guo (Process Safety and Environmental Protection, 2024)

Combined treatment with pre-aeration and carrier addition strengthens the purification performance of a deep pilot-scale duckweed-based pond - Yonggui Zhao; Jinquan Li; Yuejiao Yang; Ruidong Ma; Ying Peng; Xiaoyun Sun; Siwei Gao; Junjun Chang; Changqun Duan (Journal of Water Process Engineering, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

The incidence of asthma attributable to temperature variability: An ecological study based on 1990–2019 GBD data - Qingsong Xu; Qinfeng Zhou; Junjun Chen; Tong Li; Junxiong Ma; Runming Du; Mintao Su; Jing Li; Ming Xu; Shengzhi Sun; Jing Ma; Murugappan Ramanathan; et al. (Science of The Total Environment, 2023)

Preparation of dual-functional packaging films containing green tea essential oil microcapsules for strawberry preservation: Excellent barrier properties and antioxidant activity - Weijie Zhao; Lianjun Yu; Yali Gu; Weijia Ma; Kehui Wang; Junjun Liang; Qi Liu (Food Bioscience, 2023)

Sonoelectrochemical system mechanisms, design, and machine learning for predicting degradation kinetic constants of pharmaceutical pollutants - Yongyue Zhou; Yangmin Ren; Mingcan Cui; Fengshi Guo; Shiyu Sun; Junjun Ma; Zhengchang Han; Jeehyeong Khim (Chemical Engineering Journal, 2023)

Stabilizing Cr(Ⅲ) deriving from tannery sludge with kaolin and organic matter - Junjun Ma; Tao E; Shuyi Yang; Liang Chen; Ying Cheng; Jia Yu; Yun Li (Environmental Research, 2023)

Highly sensitive, wide-pressure and low-frequency characterized pressure sensor based on piezoresistive-piezoelectric coupling effects in porous wood - Jingjing Luo; Feihua Liu; Ao Yin; Xue Qi; Jiang Liu; Zhongqi Ren; Shiqiang Zhou; Yuxin Wang; Yang Ye; Qingzhi Ma; Junjun Zhu; Kang Li; et al. (Carbohydrate Polymers, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Comparison of effects of multiple oxidants with an ultrasonic system under unified system conditions for bisphenol A degradation - Shiyu Sun; Yangmin Ren; Fengshi Guo; Yongyue Zhou; Mingcan Cui; Junjun Ma; Zhengchang Han; Jeehyeong Khim (Chemosphere, 2023)

Zero-valent iron based materials selection for permeable reactive barrier using machine learning - Yangmin Ren; Mingcan Cui; Yongyue Zhou; Yonghyeon Lee; Junjun Ma; Zhengchang Han; Jeehyeong Khim (Journal of Hazardous Materials, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Lattice stain dominated hydrazine oxidation reaction in single-metal-element nanosheet - Jie Shi; Qintao Sun; Wenxiang Zhu; Tao Cheng; Fan Liao; Mengjie Ma; Junjun Yang; Hao Yang; Zhenglong Fan; Mingwang Shao (Chemical Engineering Journal, 2023)

Metagenomic analysis reveals patterns and hosts of antibiotic resistance in different pig farms - Bingzhen Ji; Junjun Qin; Yijia Ma; Xin Liu; Tian Wang; Guiming Liu; Bugao Li; Guoliang wang; Pengfei Gao (Environmental Science and Pollution Research, 2023)

Influence of MnO2 crystal existing form on its catalytic performance for toluene oxidation - Xuxu Zhai; Luming Li; Shuang Song; Junjun Zhang; Jun Ma; Chongrui Xie; Wei Chu (Fuel, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Relationship between meteorological factors and mortality from respiratory diseases in a subtropical humid region along the Yangtze River in China - Lingxiang Yu; Junjun Zhu; Ming Shao; Jinian Wang; Yubo Ma; Kai Hou; Huijun Li; Jiansheng Zhu; Xiaoyun Fan; Faming Pan (Environmental Science and Pollution Research, 2022)

Analysis on the hotspot characteristics of bird diversity distribution along the continental coastline of China - Peng Hou; Junjun Bai; Yan Chen; Jing Hou; Jiajun Zhao; Yutiao Ma; Jun Zhai (Frontiers in Marine Science, 2022)
Global climate change and disturbances from human activities lead to habitat loss and changes in habitat quality, resulting in a reduction in biodiversity. The continental coastline of China distributes some cities with highly developed economies and coastal wetlands with rich biodiversity, and both economic development and biodiversity conservation are important topics. In order to clarify the spatial distribution of bird biodiversity in coastal areas, based on the MaxEnt model and GIS spatial analysis, the distribution data of 488 species of birds and 15 environmental variables were used to simulate the suitable distribution areas of birds, and to analyze the spatial distribution and hotspots of bird biodiversity in coastal areas. The main findings of this study are as follows. (1) A total of 488 species in 249 genera of 21 orders and 81 families of birds were involved in the modeling of coastal areas. The main environmental factors affecting the potential distribution of birds in general are: land use, monthly mean diurnal temperature range, and precipitation of the driest month. (2) High value areas of bird richness are distributed in different locations in the four sea areas: In the Bohai Rim region, they are mainly distributed in the Liaohe Estuary Wetland in Liaoning Province, the vicinity of the Yongdingxin River and Haihe River in Tianjin, the eastern part of Tianjin, and the Yellow River and Yellow River Delta Wetland in Shandong Province; In the coastal area of the Yellow Sea, they are primarily found in Kunyu Mountain National Nature Reserve, Laoshan Provincial Nature Reserve in Shandong Province, and Yancheng Wetland Rare Birds National Nature Reserve in Jiangsu Province; In the coastal areas of the East China Sea, they are mainly found at the mouth of the Yangtze River, at the national nature reserve of Dongtan birds on Chongming Island, along the southeastern coast of Zhejiang Province, near the Min River and along the coast of Quanzhou in Fujian Province; In the coastal areas of the South China Sea, they are mainly distributed in the Pearl River Delta wetlands of Guangdong Province, the southeastern coastal areas of the Guangdong-Hong Kong-Macao Greater Bay Area, and the Shiwanda Mountain National Nature Reserve in Guangxi Province. (3) The spatial trends in the distribution of hotspots of birds of national priority protection in coastal areas are generally consistent, but more concentrated than the distribution of all birds. (4) After the high-value areas of bird richness were superimposed with protected areas, it was found that the intersecting area accounted for a small proportion of the protected area, and many areas near the inland had low bird richness. Finally, the findings provide references for bird biodiversity conservation and planning in coastal areas.

Sevoflurane-Induced Neurotoxicity in the Developing Hippocampus via HIPK2/AKT/mTOR Signaling - Lirong Liang; Ze Fan; Danyi He; Youyi Zhao; Tian Zeng; Bing Liu; Tianyuan Ma; Junjun Kang; Hui Zhang (Neurotoxicity Research, 2022)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Synthesis of 4-oxotetrahydropyrimidine-1(2H)-carboxamides derivatives as capsid assembly modulators of hepatitis B virus - Nicky Hwang; Haiqun Ban; Junjun Chen; Julia Ma; Hui Liu; Patrick Lam; John Kulp; Stephan Menne; Jinhong Chang; Ju-Tao Guo; Yanming Du (Medicinal Chemistry Research, 2021)

The miR-15/16 Cluster Is Involved in the Regulation of Vertebrate LC-PUFA Biosynthesis by Targeting pparγ as Demonostrated in Rabbitfish Siganus canaliculatus - Junjun Sun; Cuiying Chen; Cuihong You; Yang Liu; Hongyu Ma; Óscar Monroig; Douglas R. Tocher; Shuqi Wang; Yuanyou Li (Marine Biotechnology, 2020)

A probabilistic method for evaluating wedge stability based on blind data theory - Zhongjun Ma; Shengwu Qin; Junjun Chen; Jiangfeng Lv; Jianping Chen; Xiaolan Zhao (Bulletin of Engineering Geology and the Environment, 2019)

Devonian integrative stratigraphy and timescale of China - Wenkun Qie; Xueping Ma; Honghe Xu; Li Qiao; Kun Liang; Wen Guo; Junjun Song; Bo Chen; Jianfeng Lu (Science China Earth Sciences, 2019)

Comparison of single- and dual-permeability models in simulating the unsaturated hydro-mechanical behavior in a rainfall-triggered landslide - Wei Shao; Zongji Yang; Junjun Ni; Ye Su; Wen Nie; Xieyao Ma (Landslides, 2018)

Greenhouse wastewater treatment by baffled subsurface-flow constructed wetlands supplemented with flower straws as carbon source in different modes - Junjun Chang; Luyao Ma; Jinquan Chen; Yifeng Lu; Xiaoyun Wang (Environmental Science and Pollution Research, 2017)

SiRNA against Fabp5 induces 3T3-L1 cells apoptosis during adipocytic induction - Xi Ma; Xia Ren; Pengfei Han; Shengdi Hu; Junjun Wang; Jingdong Yin (Molecular Biology Reports, 2010)